Measurement of the 85Kr specific activity in the GERDA liquid argon - M. Agostini; A. Alexander; G. Araujo; A. M. Bakalyarov; M. Balata; I. Barabanov; L. Baudis; C. Bauer; S. Belogurov; A. Bettini; L. Bezrukov; V. Biancacci; et al. (European Physical Journal C: Particles and Fields)
Abstract The radioactive isotope 85Kr is found in significant quantities in the atmosphere largely due to nuclear industry. Its $${\upbeta }$$ β -decay with a half-life of 10.7 years and a Q-value of 687 keV is a dangerous background source for low-threshold noble gas and liquid detectors, which distill their detector medium from air. The Gerda experiment was operating high-purity germanium detectors immersed in a clean liquid argon bath deep underground to search for neutrinoless double beta decay with unprecedented sensitivity. The 85Kr specific activity in the liquid argon at the start of the second phase of the experiment has been determined to be $$(0.36 ± 0.03)$$ ( 0.36 ± 0.03 ) mBq/kg through an analysis of the full subsequent data set that exploits the excellent $${\upgamma }$$ γ -ray spectroscopic capabilities of Gerda.